IN SILICO DESIGN OF AMINO ACIDS-FUNCTIONALIZED IMIDAZOLES AS INHIBITORS OF DENGUE VIRUS NS3 AND NS5 PROTEINS - Mederos-Núñez, Yonatan; Pérez-Garmury, Yoan A.; Ferrer-Serrano, Armando; Rojas-Vargas, Julio A.; García-López, América (Revista Cubana de Química, 2024)
252 amino acid-functionalized imidazoles were designed to evaluate their potential as inhibitors using computational techniques. An analysis of the ADME+T profiles indicates that compounds derived from the polar amino acids Ser and Thr are the most favorable as drug candidates. Of these compounds, four (Ser-A22, Thr-A22, Ser-A35 and Thr-A35) stand out as candidates for inhibitors of proteins NS3 in their helicase domain and NS5 in their methyltransferase domain. For the NS2B-NS3Pro and NS5RdRp domains, the results are not encouraging. An analysis of the electron densities of these four compounds by DFT showed similarity with reference inhibitors in terms of frontier orbitals, reactivity and electrostatic potential surfaces, which explains the strength of the binding of these compounds with viral proteins